2021
DOI: 10.1016/j.xcrm.2021.100269
|View full text |Cite
|
Sign up to set email alerts
|

Soluble interleukin-6 receptor in the COVID-19 cytokine storm syndrome

Abstract: Data suggest that interleukin (IL)-6 blockade could reduce mortality in severe COVID-19, yet IL-6 is only modestly elevated in most patients. Chen et al. describe the role of soluble interleukin-6 receptor (sIL-6R) in IL-6 trans-signaling, and how understanding the IL-6:sIL-6R axis might help define and treat COVID-19 cytokine storm syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 15 publications
5
49
0
Order By: Relevance
“…Cytokine profiling with measurement of serum levels of the proinflammatory cytokines interleukin-5 (IL-5), IL-6, interleukin-10 (IL-10), interleukin-17A (IL-17A), interferon-gamma (IFN-g), monocyte chemoattractant protein 1 (MCP-1), and tumor necrosis factor alpha (TNF-a) in patients who developed CRS after CD3-engaging bispecific antibody APVO436 indicates that the predominant cytokine in this inflammatory cytokine response is IL-6 [58]. The administration of Tocilizumab (antibody against IL-6:IL-6R) or Siltuximab (antibody against IL-6) at standard doses with or without dexamethasone rendered APVO436-associated severe CRS manageable and rapidly transient consistent with our current understanding of the IL-6 receptor signaling [59] and the standard management of this class-specific complication [27][28][29].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Cytokine profiling with measurement of serum levels of the proinflammatory cytokines interleukin-5 (IL-5), IL-6, interleukin-10 (IL-10), interleukin-17A (IL-17A), interferon-gamma (IFN-g), monocyte chemoattractant protein 1 (MCP-1), and tumor necrosis factor alpha (TNF-a) in patients who developed CRS after CD3-engaging bispecific antibody APVO436 indicates that the predominant cytokine in this inflammatory cytokine response is IL-6 [58]. The administration of Tocilizumab (antibody against IL-6:IL-6R) or Siltuximab (antibody against IL-6) at standard doses with or without dexamethasone rendered APVO436-associated severe CRS manageable and rapidly transient consistent with our current understanding of the IL-6 receptor signaling [59] and the standard management of this class-specific complication [27][28][29].…”
Section: Discussionmentioning
confidence: 57%
“…Older patients with newly diagnosed AML respond poorly to standard induction chemotherapy and have a poor survival. For newly diagnosed older AML patients, new treatment regimens have been developed in recent years, such the combination of the BCL-2 homology 3 (BH3)-mimetic compound; Venetoclax with HMA (e.g., azacitidine/AZA and decitabine/DAC); or the combination of the Hedgehog pathway inhibitor Glasdegib with LDARAC, both of which showed significant clinical activity with reduction in the risk of death in randomized phase II clinical trials [3,4,11,59]. Older patients with relapsed AML have a dismal prognosis and are in urgent need for new salvage treatment strategies for their chemo-resistant leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we consider that validating the model in a different cohort of patients in the future would be essential to give consistency to the results. (iii) The most relevant buffering system in the COVID-cytokine storm is the IL-6: sIL-6R:sgp130 system in trans signaling, which has been described in recent publications [ 37 , 38 ]. Thus, an inherent limitation of these multi-PLEX cytokine studies is that they typically only measure the cytokine itself, whereas there are other aspects of these cytokine signaling pathways that are omitted.…”
Section: Discussionmentioning
confidence: 99%
“…Although IL-6 concentrations have been historically used as a surrogate for clinical response in chronic inflammatory conditions, recent evidence suggests that sIL-6R may be a more informative marker of immune dysregulation and a better predictor of tocilizumab response [40, 48]. Correspondingly, sIL-6R may also be a better surrogate for clinical response with tocilizumab in COVID-19.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Correspondingly, sIL-6R may also be a better surrogate for clinical response with tocilizumab in COVID-19. The proposed rationale for evaluating sIL-6R response is that trans-signaling via sIL-6R may provide a more complete picture of clinically relevant IL-6 activity in vivo [48]. Nishimoto conducted a tocilizumab PK/PD study in patients with RA and Castleman Disease and found that “as long as free tocilizumab was detectable, sIL-6R was saturated and IL-6 signaling was completely inhibited” [35].…”
Section: Introduction/backgroundmentioning
confidence: 99%